Distribution of Tyrosine Hydroxylase-Expressing Interneurons with Respect to Anatomical Organization of the Neostriatum - Unal, Bengi; Ibáñez-Sandoval, Osvaldo; Shah, Fulva; Abercrombie, Elizabeth; Tepper, James M. (Frontiers in Systems Neuroscience, 2011)
We have recently shown in vitro that striatal tyrosine hydroxylase-expressing interneurons identified in transgenic mice by expression of enhanced green fluorescent protein (TH-eGFP) display electrophysiological profiles that are distinct from those of other striatal interneurons. Furthermore, striatal TH-eGFP interneurons show marked diversity in their electrophysiological properties and have been divided into four distinct subtypes. One question that arises from these observations is whether striatal TH-eGFP interneurons are distributed randomly, or obey some sort of organizational plan as has been shown to be the case with other striatal interneurons. An understanding of the striatal TH-eGFP interneuronal patterning is a vital step in understanding the role of these neurons in striatal functioning. Therefore, in the present set of studies the location of electrophysiologically identified striatal TH-eGFP interneurons was mapped. In addition, the distribution of TH-eGFP interneurons with respect to the striatal striosome-matrix compartmental organization was determined using µ-opioid receptor (MOR) immunofluorescence or intrinsic TH-eGFP fluorescence to delineate striosome and matrix compartments. Overall, the distribution of the different TH-eGFP interneuronal subtypes did not differ in dorsal versus ventral striatum. However, striatal TH-eGFP interneurons were found to be mostly in the matrix in the dorsal striatum whereas a significantly higher proportion of these neurons was located in MOR-enriched domains of the ventral striatum. Further, the majority of striatal TH-eGFP interneurons was found to be located within 100 µm of a striosome-matrix boundary. Taken together, the current results suggest that TH-eGFP interneurons obey different organizational principles in dorsal vs. ventral striatum, and may play a role in communication between striatal striosome and matrix compartments.